2020
DOI: 10.1126/science.aaw2601
|View full text |Cite
|
Sign up to set email alerts
|

Vertebrate diapause preserves organisms long term through Polycomb complex members

Abstract: Diapause is a state of suspended development that helps organisms survive extreme environments. How diapause protects living organisms is largely unknown. Using the African turquoise killifish (Nothobranchius furzeri), we show that diapause preserves complex organisms for extremely long periods of time without trade-offs for subsequent adult growth, fertility, and life span. Transcriptome analyses indicate that diapause is an active state, with dynamic regulation of metabolism and organ development genes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 47 publications
2
72
2
Order By: Relevance
“…Several laboratories are currently investigating the age-related phenotypes of genetically modified N. furzeri lines. Specific knock-out lines that have been generated in this species are Tert −/− [ 43 ] and Cbx7 −/− [ 44 ]. In the first case, the transgenic line was produced as a proof of concept of the CRISPR/Cas9-based genome editing approach; the gene was chosen to gain insights into the role of telomerase during aging (see also [ 44 ]).…”
Section: Major Interests and Research Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several laboratories are currently investigating the age-related phenotypes of genetically modified N. furzeri lines. Specific knock-out lines that have been generated in this species are Tert −/− [ 43 ] and Cbx7 −/− [ 44 ]. In the first case, the transgenic line was produced as a proof of concept of the CRISPR/Cas9-based genome editing approach; the gene was chosen to gain insights into the role of telomerase during aging (see also [ 44 ]).…”
Section: Major Interests and Research Questionsmentioning
confidence: 99%
“…Specific knock-out lines that have been generated in this species are Tert −/− [ 43 ] and Cbx7 −/− [ 44 ]. In the first case, the transgenic line was produced as a proof of concept of the CRISPR/Cas9-based genome editing approach; the gene was chosen to gain insights into the role of telomerase during aging (see also [ 44 ]). The second transgenic line was specifically created to investigate the role of Polycomb genes in diapause regulation [ 44 ].…”
Section: Major Interests and Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…N. furzeri was demonstrated to be an invaluable tool for studies in disparate branches of investigation such as evolutionary genomics (Reichwald et al, 2015;Valenzano et al, 2015;Sahm et al, 2017;Cui et al, 2020), regenerative medicine (Wendler et al, 2015), developmental biology (Dolfi et al, 2019;Hu et al, 2020), pharmacology (Valenzano et al, 2006;Baumgart et al, 2016) and ecotoxicology (Philippe et al, 2018). It was also shown that N. furzeri presents spontaneous age-dependent gliosis (Tozzini et al, 2012), neuronal protein aggregation and loss of stoichiometry of protein complexes in the brain that is triggered by early impairment of proteasome activity (Kelmer Sacramento et al, 2020) with selective agedependent degeneration of dopaminergic and noradrenergic neurons in the midbrain (Matsui et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…S1A) hatch in the absence of food ( 31 ), and expression of operons increases markedly during recovery from the L1 arrest ( 30 ). Vertebrate diapause was also recently shown to help organisms to survive long periods of time in extreme environments without trade-off for subsequent growth and fertility ( 32 ).…”
Section: Introductionmentioning
confidence: 99%